A radio frequency (RF) energy harvester - Soh, Wee Kiong (2016)
In the modern world now, wireless communication is getting more and more common as compared to wired communication due to the ease of transmission to multiple location wirelessly. The communication is no longer bounded and restrain by the length of wire. Wireless communication device such as Bluetooth, Wi-Fi router, remote control, cordless phone and so on uses the 2.4 GHz Radio Frequency (RF) spectrum as it is an unlicensed spectrum. It spectrum is also shared with the Industrial, Scientific, and Medical (ISM) devices. Due to the widespread of wireless device, the amount of 2.4 GHz signal available in the surrounding is tremendous. This suggested that power can be harvested from the signal transmitted from the wireless devices. A Final Year Project (FYP) studying on the harvesting of energy from the 2.4 GHz spectrum was conducted. In this FYP, I will learn and required to design and implement an RF energy harvester to harvest the energy available in the 2.4 GHz RF spectrum. The RF energy harvester will consist of an antenna, an impedance matching network, an AC to DC rectifier and a capacitor for voltage smoothing and storage of energy harvested. A voltage multiplier or booster might be needed to achieve the voltage required for the load.